Efeito do manejo de cobertura sobre índices de conforto térmico, variáveis fisiológicas e desempenho de bezerros Leiteiros - (:unkn) unknown (Universidade Estadual de Goiás, 2010)
This study compared the management of coverage in individual shelters for calves on indexes of thermal comfort, physiological responses, weight gain and food consumption. To evaluate the thermal comfort index was used completely randomized design with three treatments and 59 repetitions, and the repetitions measures in time. The treatments were: Z - Galvanized zinc, 26 mm thick, CA – Asbestos cement and CAB - Asbestos cement painted white. Were collected as environmental variables within the shelters, black globe temperature (BGT), relative humidity (RH) and dry bulb temperature (Dnt), parameters used to calculate the heat index, index of black globe temperature (WBGT), mean radiant temperature (MRT) and radiant heat load (RHL). The data were collected at 9:00 am, 11:00 am and 1:00 pm, and day as repetition. The external environmental data, Dnt, RH, wind speed (W) and dew point (Dp), were collected by a meter, model LS8000. Found 523.44 Wm-2, 506.72 Wm-2 489.28 Wm-2 for RHL for the treatment galvanized zinc (Z), asbestos cement (CA) and asbestos cement painted white (CAB), respectively, demonstrating that CA and CAB received a similar performance and Z showed an environment with greater environmental discomfort. For analysis of animal performance used completely randomized design with factorial arrangement of treatments 2 X 3: two sexies and three coverage managements (Z, CA and CAB). We used 18 animals, nine of each sex, randomly distributed among the treatments. The experiment lasted 70 days. The physiologicals characteristics analyzed were rectal temperature and respiratory rate, above as daily weight gain, feed conversion and consumption of dry matter. The data were analyzed by computational program SISVAR (free), comparing the means by Tukey test, adopting a significance level of 5%. There was an increase in respiratory rate (RR) for males, 65.92 mov.min-1 (P<0.05), as the females had an average 60.37 mov.min-1. For rectal temperature (RT) there wasn’t difference between treatments. Different coverage didn’t influence performance and food consumption, however, interfere with the physiology of thermoregulation of animals.
Keywords: Índices térmicos, .; Termorregulação; Ganho de peso; Bezerros leiteiros; Consumo de ração; Indexes thermal; Thermoregulation; Weight gain; Dairy calves; Feed intake; ENGENHARIA AGRICOLA::CONSTRUCOES RURAIS E AMBIENCIA